U.S. politics as a reminder of historical losses in American Indian Adults: Implications for political participation - Zachary J. Wood; Peter J. Helm; Neha A. John-Henderson (PLoS ONE, 2025)
Historical loss (HL) is a contributor to experiences of historical trauma and its negative impacts on American Indians. The relationship between HL, U.S. politics and political participation among American Indians has not been examined. Minority groups can become politically active through perceiving discrimination or injustices against them. Measures of HL contain items related to the discrimination and injustices that American Indians have experienced. While the Historical Loss Scale (HLS) measures the frequency with which American Indians think about HL, it does not measure the degree to which U.S. Politics may act as a reminder of HL. Here, we introduce an adaptation of the HLS: the U.S. Politics as a Loss Reminder Scale (USPLRS), measuring the degree to which U.S. politics may remind American Indian adults of HL, with higher scores reflecting a greater association between U.S. politics and HL. A sample of 877 American Indian adults completed a series of questionnaires including the HLS, USPLRS, and measures of political participation during the November 2020 national election cycle. Results revealed a 3-factor structure of the USPLRS related to losses due to Government Mistreatment, Interpersonal Loss, and Respect. Scores on both the HLS and USPLRS were positively associated with political participation, with the USPLRS exhibiting incremental validity beyond the HLS.